CORRELATION BETWEEN TONSIL HYPERTROPHY AND ALLERGIC RHINITIS IN CHILDREN - Kopacheva-Barsova, Gabriela; Dukovska, Vesna; Nikoloska, Sofija; Trajkov, Dejan (Journal of Morphological Sciences, 2020)
To show whether there is a correlation between the tonsils hypertrophy and adenoid hypertrophy (AH) with allergic rhinitis in children in R. Macedonia. A total of 120 children (5.3 Â± 1.2 years old) with tonsil hypertrophy, adenoid hypertrophy, persistent upper respiratory infections and consecutive nasal obstruction were examined, after their parents gave a verbal consent for their participation. Inclusion criteria were: frequent upper respiratory infections, angina, nasal congestion due to nasal obstruction caused by adenoid hypertrophy, frequent serous otitis due to adenoid hypertrophy and sleep apnea due to tonsil hypertrophy. The prevalence of allergic rhinitis (AR) was as follows: AR had 70% of children with concha nasal hypertrophy, 39.2% of children with tonsillar hypertrophy, and 78.3% of children with adenoid hypertrophy. Although in the group of children with adenoid hypertrophy, a more severe degree of nasal concha hypertrophy was registered in children with AR compared to children without AR, it was statistically not significant. Regarding children with adenoid hypertrophy (AH), the results showed that children with AR presented significantly different results for Parikh's scale (p = 0.0076). Obstruction of torus tubarius was more common in children with AR (86.8% vs . 61.2%), while these children had a finding of soft palate obstruction (9.4% vs. 26.8%), and vomer obstruction (3.8% vs. 11.9%) less often than children without AR. Our study found that almost half of the children with tonsillitis/adenoid hypertrophy had AR. Grade 3 and 4 TH was present in third of the children. Keywords :  allergic rhinitis, children, nasal concha, volume of palatine tonsils, volume of adenoid vegetation, correlation